PENGARUH PEMAHAMAN AKUNTANSI DASAR, COMPUTER ANXIETY, COMPUTER ATTITUDE, DAN FAKTOR SOSIAL TERHADAP MINAT MAHASISWA AKUNTANSI DALAM MENGOPERASIKAN SOFTWARE AKUNTANSI (Studi Kasus pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi Universitas Flores) - Asiah, Nur; Mаrselinа, Аpriаnа; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2024)
This study aims to test whether there is an effect of Basic Accounting Understanding, Computer Anxiety, Computer Attitude, and Social Factors on Accounting Students' Interest in Operating Accounting Software (Case Study on Students of the Accounting Study Program, Faculty of Economics, University of Flores). In this study there were several problems such as the results of previous studies that were inconsistent, where the variables of basic accounting understanding, computer anxiety, computer attitude and social factors do not influence students’ interest in operating accounting software, the authors also conducted a pre-survey initial regarding the problems faced by students in operate accounting software.This research is a quantitative research. This study uses data collection techniques with a questionnaire. Primary data were obtained directly from the respondents through filling out questionnaires which were distributed directly, while secondary data in the form of theories and other supporting data were obtained from the literature. The population in this study were students in the Accounting Study Program, the Faculty of Economics, University of Flores, with a total of 546 people. This study used non-probability sampling with a sampling technique using purposive sampling with a total sample of 128 people, and used SPSS 25 as a research data processor. The results of the study show that the basic understanding of accounting has an effect on the interest of accounting students in operating accounting software. This is evidenced by the value of the regression coefficient of understanding basic accounting of 0.473 with a t-count value of (2.693 > 1.978) with a significant level of (0.008 <0.05). Computer anxiety affects the interest of accounting students in operating accounting software. This is evidenced by the value of the regression coefficient of computer anxiety of 0.174 with a t-count value of (2.269> 1.978) with a significant level of (0.025 <0.05). Computer attitude has an effect on the interest of accounting students in operating accounting software. This is evidenced by the value of the regression coefficient of computer attitude of 0.183 with a t-count value of (3.926 > 1.978) with a significant level of (0.000 <0.05). and the social factor variable has no effect on the interest of accounting students in operating accounting software. This is evidenced by the value of the regression coefficient social factor of 0.134 with a t-count value of (0.564 <1.978) with a significant level of (0.574 > 0.05). Simultaneously the variables of basic accounting understanding, computer anxiety, computer attitude and social factors together influence the interest of accounting students at the Faculty of Economics, University of Flores in operating accounting software by 33.5%, while the remaining 66.5% is influenced by other variables that are not accepted. sport in research.